Analisis Dan Rancang Bangun Sistem Layanan Proxy Server Pada SMK Unggul Sakti Jambi - Santoso, Santoso; Assegaff, Setiawan (Jurnal Manajemen Sistem Informasi, 2017)
More advanced information technology has an important role that can be used as tools in all fields it is supported by the development of the internet is so rapid and increasingly competitive cost Internet access. But the problems that occur when no in filters that can lead to healthy Internet abuse, which should be used to help find positive information, can actually open access negative sites. The government can not fully block porn sites, hence the need for filtering access to the internet which can be filtered or blocked by the proxy server facility. The goal of this research is to build a system that utilizes a proxy server to secure access to information that avoid negative information or that is not good for the school environment. Proxy server service system is one of the reliable alternative in creating a healthy or positive internet access so as to raise the matter with the building services system that uses a proxy server Debian 6 Linux Operating System and its use Squid proxy application.